Pemberantasan Tindak Pidana Korupsi di Masa Pandemi Beserta Kinerja KPK Dalam Penanganannya - Urbanisasi; Columbanus Priaardanto (Jurnal Kewarganegaraan, 2023)
Abstract The crime of corruption is one of several special criminal acts that become an urgency in the life of the state in Indonesia, the rise of corruption crimes that occur among the government is increasingly soaring and rising, the role of the KPK (Corruption Eradication Commission) in the midst of this problem has not been seen, coupled with various obstacles that arise both from the KPK and from kpk enemies who make the law become Hampered. In the midst of a difficult situation during the Covid-19 pandemic, power officials often take advantage of difficult situations and grief that is soeable in the community as an income field for those who certainly do not care about human values and justice, they take advantage of the difficult situation in the midst of the Covid-19 Pandemic to reap various benefits ranging from the alleged involvement of officials such as ministers and heads of institutions in the PCR business to embezzlement in the distribution of community social assistance funds to people stranded from Covid-19. Keywords: Corruption, Corruption Eradication Commission